PENGARUH ARTIFICIAL INTELLIGENCE (AI) DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Sektor Consumer Goods Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Maharani Saskia Putri; Wahyu Meiranto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of AI disclosure on firm value in non cyclical consumer goods companies listed on the Indonesia Stock Exchange for the 2022–2024 period. Furthermore, this study examines the role of financial performance as a mediating variable in the relationship between AI disclosure and firm value. This is conducted amidst the increasing adoption of AI as a strategic capability that has the potential to influence market perceptions of firm value. The study employed a quantitative approach with secondary data sourced from annual reports and financial reports on the official IDX and Bloomberg websites. The sample was selected using a purposive sampling method, resulting in 66 companies with a total of 198 observations over the three-year study period. AI disclosure was measured using content analysis-based AI Frequency Disclosure (AIFREC), firm value was measured using Tobin's Q, and financial performance was proxied by Return on Assets (ROA). Hypotheses were tested using panel data regression analysis and Aroian's mediation test. The results of the study indicate that AI disclosure has a negative and insignificant effect on both firm value and financial performance. While financial performance has a positive and significant effect on firm value, it fails to mediate the relationship between AI disclosure and firm value. This indicates that the market does not yet consider AI disclosure a credible signal without concrete evidence of company performance. Therefore, AI disclosure will be more meaningful to the market if supported by financial performance that reflects the effectiveness of AI implementation in company operations.